Foreign Help Wanted : Easing Japan's Labor Shortages - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2015)
Data and anecdotal evidence suggest that Japan is suffering from labor shortages, which are large in an international perspective, have a negative impact on potential growth, and reduce the effectiveness of monetary and fiscal stimulus. This paper focuses on policy options to ease Japan's labor shortages. In particular, we focus on possible measures to increase reliance on foreign labor. Other policy recommendations to deal with shortages include policies aimed at increasing female labor participation, encouraging wage growth, increasing investment, as well as training and other active labor market policies.